IOT Based unmanned surface vehicle for water sampling and water quality application - Haris Faisal, Shaharuddin; Zainah, Md. Zain (2021)
Water bodies around the world are mostly left unmonitored. Moreover, there are lot of risk and cost involved to monitor the water quality manually. With using a set of sensors on a remotely control water vehicle the risk and cost can be reduced.